Parametric studies of thin film nickel catalyst for the growth of carbon nanotubes - Saidin, Mohammad Abdul Razis; Aziz, Madzlan; Ismail, Ahmad Fauzi (Penerbit UTM Press, 2008)
The thickness and morphology of the catalyst film significantly affect the properties of carbon nanotubes (CNTs). The catalyst size and shape are the key factors for the controlling of CNT diameter. The objectives of this study are to develop a thin catalyst film for CNTs growth application by varying the time of deposition and investigate the effect of radio frequency (rf) plasma power. The thin catalyst film was developed using physical sputtering method with an rf power between 20 to 100 watt at varying deposition time with nickel as a catalyst. The Ni/Cr film in this study was fabricated on corning glass substrates. The thin film nickel catalyst was obtained with a thickness of 12 nm using surface profiler and was characterized using field emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM) to determine the morphologies and particle size of the catalyst. The rf power and deposition time is found remarkably influence the catalyst morphology. Higher power supply are found to be more effective for scattering the catalyst thin film, homogeneous and uniform thin film on the substrate.